Discurso, política e infotainment : uma análise discursiva do CQC - Gon, Laura Colli (2012)
Nowadays the amount of academic researchers enrolled with Political and Social Sciences and also with Language Sciences is increasingly growing, which take political events as objects of reflection. However, there are few researches although they are increasing researches- that focus on the placement of these political events on television shows that are part of cyber culture. This study tries to cope with reflection on the placement of political events on the television show CQC (Custe o Que Custar), especially on the composition of its articulation with discursive scenography and with the cyber culture, especially on the study of the so called Infotainment (discourse produced by studying information and entertainment working together). In this investigation, we analyzed four programs shown on September and October of 2010, during the first round of presidential elections in Brazil. To make our goal, which is based on the comprehension of the corpus studied we seek shelter in the theoretical and methodological guidance of French Discourse Analysis especially on Dominique Maingueneau s studies, focusing on the author s ideas on the scene of enunciation : encompassing scene; generic scene and scenography. In addition to that, we also support this study on Oswald Ducrot s polyphonic theory. The methodological procedure is seeking and understanding the images that built the show s discursive scenography our focus is always guided by the interface between description and interpretation, explaining the regularities created by this object of study. We will start the research by discussing what previous studies had studied about the CQC as an object, this is followed by a discussion of the program as a discourse gender and, finally we discuss its discursive scenography s. The results of this study argue that the genre of discourse and historical events are two processes that work together towards the constitution of the interviews scenography from the television show CQC.